Pancreatic islet of Langerhans' cytoarchitecture and ultrastructure in normal glucose tolerance and in type 2 diabetes mellitus. (19th September 2018) - Folli, Franco; La Rosa, Stefano; Finzi, Giovanna; Davalli, Alberto M.; Galli, Alessandra; Dick, Edward J.; Perego, Carla; Mendoza, Rodolfo Guardado
Abstract : While a number of structural and cellular abnormalities occur in the islet of Langerhans in diabetes, and in particular in type 2 diabetes, the focus has been mostly on the insulin producing β‐cells and only more recently on glucagon producing α‐ and δ‐cells. There is ample evidence that in type 2 diabetes mellitus (T2DM), in addition to a progressive decline in β‐cell function and associated insulin resistance in a number of insulin‐sensitive tissues, alterations in glucagon secretion are also present and may play an important role in the pathogenesis of hyperglycemia both in the fasting and in the postprandial state. Recently, a number of studies have showed that there are also functional and structural alterations in glucagon‐producing α‐cells and somatostatin‐producing δ‐cells. Thus, it is becoming increasingly clear that multiple cellular alterations of multiple cell types occur, which adds even more complexity to our understanding of the pathophysiology of this common and severe disease. We believe that persistent efforts to increase the understanding of the pathophysiology of hormone secretion in the islets of Langerhans will also improve our capability to better prevent and treat diabetes mellitus.